Use of Lactobacillus fermentum for improving fermentation degree of smallholder dried cocoa beans - Ariza Budi Tunjung-Sari; Misnawi Jati; Noor Ariefandie Febrianto; Teguh Wahyudi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2019)
In an attempt to improve the quality of dried cocoa beans produced from small holder farming in Indonesia, experiment of cocoa beans and Lactobacillus fermentum (LF) was conducted. LF culture at concentration 5% w/w was added into dried cocoa beans and incubated for four days. Treated beans were sun dried and evaluated for slaty and purple appearance on the nibs, as well as defects and sensory quality. This study reports a significant decrease in the proportion of slaty and purple beans in the treated groups either in smaller (30 kg) or in the larger (150 kg) scales. The moulded bean number surged, but moulded beans was already present in the untreated group. The sensory profile was obtaining higher scores on the chocolate flavor, bitterness and astringency attributes. It is concluded that LF culture could be used for improving the physical and sensory qualities of cocoa beans from small holder farmers.